2017
DOI: 10.1016/j.sjbs.2017.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Bio-functionalized gold nanoparticles: Benign effect in Sprague-Dawley rats by intravenous administration

Abstract: Gold nanoparticles offer a great promise in clinical research. Despite various applications of the metal nanoparticles it is challenging to implement in clinical applications This aspect is deprived of understanding the biological mechanisms that occurs in the cells. In this report we have evaluated application of AuNP on the safety profile at different doses (100, 200, and 500 μg/kg Bwt/day) on intravenous administration in rats regularly for 28 days. The study was performed based on the OECD test guideline 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Previous studies to understand the cytotoxicity of AuNPs showed that AuNPs did not show any toxicity compared to gold ions [58]. "Parveen et al [59 ] confirmed that" AuNP administration showed no toxicity in the day-to-day activity of male and female rats. Besides, the continuous administration of AuNPs intra-articular has no toxic effects on the internal organs (lungs, kidneys, spleen, and liver) [60].…”
Section: Histopathology and Relative Weight Of The Heartmentioning
confidence: 97%
“…Previous studies to understand the cytotoxicity of AuNPs showed that AuNPs did not show any toxicity compared to gold ions [58]. "Parveen et al [59 ] confirmed that" AuNP administration showed no toxicity in the day-to-day activity of male and female rats. Besides, the continuous administration of AuNPs intra-articular has no toxic effects on the internal organs (lungs, kidneys, spleen, and liver) [60].…”
Section: Histopathology and Relative Weight Of The Heartmentioning
confidence: 97%
“…They are characterized by wide systemic distribution that is inversely correlated with their sizes [21,22] . The smaller particles offered wide systemic distribution to brain, kidney, lungs, liver, heart, spleen, thymus and reproductive organs [23,24] . GNPs can also damage genes leading to inflammation and cell death [25,26] .…”
Section: Introductionmentioning
confidence: 99%